General resource for ionospheric transient investigations (GRITI): An open-source code developed in support of the Dinsmore et al. (2021) results - Dinsmore, Ross; Mathews, J.D.; Urbina, Julio (MethodsX, 2021)
The analysis techniques and the corresponding software suite GRITI (General Resource for Ionospheric Transient Investigations) are described. GRITI was used to develop the Dinsmore et al. [2] results, which found a novel classification of traveling ionospheric disturbances (TIDs) called semi-coherent ionospheric pulsing structures (SCIPS). The any-geographic range (local-to-global), any-azimuth angle keogram algorithm used to analyze SCIPS in that work is detailed. The keogram algorithm in GRITI is applied to detrended vTEC (vertical Total Electron Content) data, called delta-vTEC herein, in Dinsmore et al. [2] and the follow-on paper Dinsmore et al. [3], but is also applicable to any other two-dimensional dataset that evolves through time. GRITI's delta-vTEC processing algorithm is also described in detail, which is used to provide the delta-vTEC data for Dinsmore et al. [3]. •We detail a keogram algorithm for analysis of delta-vTEC data in Dinsmore et al. [2] and the follow-on paper Dinsmore et al. [3].•We detail a delta-vTEC processing algorithm that converts vTEC data to delta-vTEC through detrending that is used to provide the delta-vTEC data used in Dinsmore et al. [3].•GRITI is an open-source Python 3 analysis codebase that encompasses the delta-vTEC processing and keogram algorithms. GRITI has additional support for other data sources and is designed for flexibility in adding new data sources and analysis methods. GRITI is available for download at: https://github.com/dinsmoro/GRITI. [Display omitted]